APLIKASI SETTING DNS SERVER BERBASIS WEB PADA LINUX UBUNTU SERVER - Ertama Putra, Hirga; ., Syahminan (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
With many Linux Operating System, automatically many Linux users. From the start of the installation of the Operating System, Linux has 2 modes for zoom (Interface), the TEXT mode and mode GUI (Graphic User Interface). To TEXT mode is usually used for servers that promotes speed and efficiency of hard drive capacity. For GUI mode is used for desktop computers, because it is easy to operate with excellence zoom an image. Based on the above background, it is concluded several issues, among others: 1.Bagaimana how application installation on Linux Ubuntu Server? 2.Bagaimana how to configure Ubuntu Server Linux server remotely? 3Bagaimana how WEB-based DNS server settings on Ubuntu Linux Server? The purpose of the study is as follows: 1.Mempermudah setting up a server without having to be in front of the server machine. 2.Mensetting server does not use the text but using the GUI. 3. No need additional applications, just using the WEB Browser to run it.Â Keywords : Ubuntu, mode text, mode gui, DNS, Web Server